Depression, anxiety, and psychosocial stressors across BMI classes: A Norwegian population study - The HUNT Study - Eik-Nes, Trine Tetlie; Tokatlian, Audrey; Raman, Jayanthi; Spirou, Dean; Kvaløy, Kirsti (Frontiers in Endocrinology, 2022)
Background: Obesity is a global issue with detrimental health impacts. Recent research has highlighted the complexity of obesity due to its psychological correlates. The purpose of the present study was to explore the relationship between body mass index (BMI) and depression, anxiety, and psychosocial stress. Methods: Data, including demographic, height, and weight information from 23 557 adult participants was obtained from the fourth survey of the Norwegian population based Trøndelag Health Study (HUNT4, 2017-2019). The Hospital Anxiety and Depression Scale (HADS) was used to measure self-reported depression and anxiety. We also collected data on 10 domains of psychosocial stress (violence, mental violence, unwanted sex, cyber bullying, school bullying, history of own life-threatening disease, life-threatening disease in family, relationship problems, divorce, and sudden family death), which were aggregated into a cumulative measure of psychosocial stress. Results: Multinomial logistic regression was utilised for statistical analysis. In the full model, the relationship between depression, anxiety, and psychosocial stress were explored controlling for age, sex, income, marital status, and educational attainment. After adjustments, a significant relationship was found between depression and obesity I (OR = 1.05, 95% CI 1.03-1.06, p < .001) and II and III (OR = 1.10, 95% CI 1.06-1.14, p < .001). After the same adjustments, significant relationship between anxiety and overweight and obesity class I was found among elderly participants (>65 years old). Psychosocial stress significantly and positively related to all levels of BMI, with or without considering anxiety and depression, after controlling for sex, age, educational attainment, marital status, and income in all age groups. Conclusions: Obesity is a multifaceted health problem, significantly related to psychological factors including depression and psychosocial stress, which supports the need for a multifaceted, targeted approach to obesity treatment.